Association between combat-related traumatic injury and cardiovascular risk. Issue 5 (25th November 2021) - Boos, Christopher J; Schofield, Susie; Cullinan, Paul; Dyball, Daniel; Fear, Nicola T; Bull, Anthony M J; Pernet, David; Bennett, Alexander N
Abstract : Objective: The association between combat-related traumatic injury (CRTI) and cardiovascular risk is uncertain. This study aimed to investigate the association between CRTI and both metabolic syndrome (MetS) and arterial stiffness. Methods: This was a prospective observational cohort study consisting of 579 male adult UK combat veterans (UK-Afghanistan War 2003–2014) with CRTI who were frequency-matched to 565 uninjured men by age, service, rank, regiment, deployment period and role-in-theatre. Measures included quantification of injury severity (New Injury Severity Score (NISS)), visceral fat area (dual-energy X-ray absorptiometry), arterial stiffness (heart rate-adjusted central augmentation index (cAIx) and pulse wave velocity (PWV)), fasting venous blood glucose, lipids and high-sensitivity C reactive protein (hs-CRP). Results: Overall the participants were 34.1±5.4 years, with a mean (±SD) time from injury/deployment of 8.3±2.1 years. The prevalence of MetS (18.0% vs 11.8%; adjusted risk ratio 1.46, 95% CI 1.10 to 1.94, p<0.0001) and the mean cAIx (17.61%±8.79% vs 15.23%±8.19%, p<0.0001) were higher among the CRTI versus the uninjured group, respectively. Abdominal waist circumference, visceral fat area, triglycerides, estimated insulin resistance and hs-CRP levels were greater and physical activity and high-density lipoprotein-cholesterol lower with CRTI. There were no significant between-group differences in blood glucose, blood pressure or PWV. CRTI, injury severity (↑NISS), age, socioeconomic status (SEC) and physical activity were independently associated with both MetS and cAIx. Conclusions: CRTI is associated with an increased prevalence of MetS and arterial stiffness, which are also influenced by age, injury severity, physical activity and SEC. The longitudinal impact of CRTI on clinical cardiovascular events needs further examination.